DEVELOPMENT OF THE ACTIVITY OF THE BANKING SYSTEM IN THE CONDITIONS OF INNOVATIVE DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2024)
The article examines the development and improvement of banking activities in the context of diversification, identifies the priority directions of development of the banking services market. The directions of improving their elements and mechanisms of the banking services market are substantiated, the characteristic features of the development of banking activities and their impact on the social and economic development of the Republic of Uzbekistan are highlighted and described.